Innovating for the Global South Towards an Inclusive Innovation Agenda - Soman, Dilip; Gross Stein, Janice; Wong, Joseph (Munk Series on Global Affairs, 2018)
Despite the vast wealth generated in the last half century, in today’s world inequality is worsening and poverty is becoming increasingly chronic. Hundreds of millions of people continue to live on less than